Validating the psychometric properties of the anxiety subscale of the DASS-21 - Dwamena, Ama Amponsah; Osei, Mavis (Nairobi Journal of Humanities and Social Sciences, 2024)
Anxiety is a recognized negative activated emotion characterized by constant worry and uncertainty of a situation or outcome. Although worrying may be an everyday activity, excessive and frequent traits can impair academic functioning. The study thus aimed to validate the psychometric properties of the anxiety subscale of the DASS-21 among a non-clinical sample of visual art students and ascertain their existent level of anxiety. Using a cross-sectional survey design, a hundred and fifty visual arts students from KNUST senior high school, Ghana, completed a questionnaire containing the anxiety subscale of the DASS-21 and some demographic details. Analysis was done using JAMOVI. It was revealed that more than two-thirds of the sample fell within the ratings of moderate anxiety level to extremely severe anxiety. Besides, female visual arts students reportedly had a slightly higher anxiety level (m= 16.4, SD=9.07) than their male counterparts m=12.7, SD= 8.86) using the mean figures of the total anxiety score. The anxiety subscale had commendable psychometric properties and its reliability and ease of administering will enhance the diagnoses and research on anxiety among senior high school students in Ghana.